An experimental study of static and dynamic behaviour of bolted end-plate joints of steel. (November 2015) - Grimsmo, E.L.; Clausen, A.H.; Langseth, M.; Aalberg, A.
Abstract: Many actions, such as accidental or malicious explosions, may impose high loading rates to structural frames. To enhance the knowledge of the behaviour of joints subjected to severe impulsive loading, a double-sided beam-to-column joint configuration was tested at quasi-static and dynamic loading rates. The test specimens consisted of H-section beams and columns, extended end-plates, and high-strength bolts. In both the quasi-static and dynamic tests, the fracture modes were bolt failure in combination with plastic deformation of the end-plates. However, it was observed that the joints absorbed considerably more energy before failure in the dynamic tests than in the quasi-static tests, partly due to changes in the deformation modes. Also, the ductility of the joints seemed to increase for higher loading rates. These results suggest that the tested joints behave in a preferable manner under extreme impulsive loads. Highlights: Double-sided beam-to-column steel joint configurations have been tested at quasi-static and dynamic load conditions. End-plate bending deformation and tensile fracture of the bolts were the failure modes for both load rate regimes. Noticeable shear deformation of the bolts was experienced in the dynamic tests. The joint configurations seemed to become more ductile and absorb more energy in the dynamic tests.